Impact of temperature on EC50 of ropivacaine in axillary brachial plexus blocks: based on Dixon’s up-and-down method - Wang, Alin; Shao, Yunhao; Zheng, Yuling; Li, Xiaoling; Huang, Bixin; Mai, Ying; Zhang, Zhongqi (Frontiers in Medicine, 2025)
ObjectiveThe efficacy of local anesthetics like ropivacaine in axillary brachial plexus blocks may be influenced by temperature, though its impact on the median effective concentration (EC50) remains unclear. This study aimed to determine the EC50 of ropivacaine at room temperature (RT, 23°C) and body temperature (BT, 37°C) using the Dixon’s up-and-down method.MethodsFifty-nine patients scheduled for upper limb surgery under ultrasound-guided brachial plexus block with ropivacaine were randomly divided into the RT group or BT group, with ropivacaine stored at 23°C for the RT group and 37°C for the BT group. The ropivacaine concentration for each subsequent patient was determined using the up-and-down method. If the sensory nerve block met surgical incision requirements within 30 min, it was classified as “Effective”; otherwise, it was classified as “Ineffective.” For “Effective” cases, the ropivacaine concentration was reduced by 0.05% for the next patient, while for “Ineffective” cases, it was increased by 0.05%. The initial ropivacaine concentration was set at 0.5% for both groups. Probit regression analysis was then used to determine the EC50 of ropivacaine. The primary outcome was EC50 of ropivacaine, calculated using probit regression. Secondary outcomes included surgical processes indicators and adverse events.ResultsThe EC50 of ropivacaine was significantly lower in the BT group (0.175, 95% CI: 0.109–0.220%) compared to the RT group (0.243, 95% CI: 0.171–0.289%) (p < 0.001). Time to surgical readiness was longer in the BT group (median 25 vs. 13 min, p < 0.001), but no differences were observed in adverse events.ConclusionWarming ropivacaine to 37°C reduces the EC50 of ropivacaine for axillary brachial plexus blocks, suggesting that lower concentrations may achieve effective anesthesia. These findings highlight temperature as a modifiable factor to optimize local anesthetic dosing, potentially minimizing toxicity risks while maintaining efficacy.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=28438 Identifier, ChiCTR1800016721.